Procedures of commencing a civil suit : a comparative analysis between Malaysia and India - Shahrul Mizan Ismail; Vinoshen Raveentharan; Darrshini S. Murgan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Generally, the civil suit is when Plaintiff can seek to hold Defendant liable for a few types of harm or wrongful act. Before commencing a civil suit or advising the client on filing a civil suit, there are five factors that need to be considered. The five factors include cause of action, limitation period, parties to the suit, jurisdiction and mode of commencement. Next, there are two modes of commencement of civil suits in Malaysia. The modes are the Writ and Originating Summons. The Writ must be filed by the Plaintiff either by their Solicitor or personally in court. This is the first step in commencing a civil proceeding. Writ is one of the examples in the originating process and a formal document that will be addressed to the defendant, which serves to notify them of the proceedings. It is a letter of demand in setting out the claims against the recipient. Next, the Originating Summons is suitable for the Plaintiff or Applicant who intends to make an application under statutory provisions. There are a few differences between the mode of commencement by Writ and Originating Summons. The objective of the article is to understand the procedures for commencing a civil suit. Hence, qualitative writing is based on primary and secondary sources. A comparative analysis has been conducted to compare the procedures for commencing a civil suit between Malaysia and India. The comparative analysis compares and highlights the mode of commencement in Malaysia and India and recommends ways to improvise the mode of commencement in Malaysia. Hence, this paper suggests that more comprehensive and detailed modes of commencement must be included in Malaysia.